Role of carbohydrate in central fatigue: a systematic review - Khong, T. K.; Selvanayagam, V. S.; Sidhu, S. K.; Yusof, A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Carbohydrate (CHO) depletion is linked to neuromuscular fatigue during exercise. While its role at peripheral level is relatively well understood, less is known about its impact centrally. The aim of this systematic review was to critically analyze the effects of CHO on central fatigue (CF) assessed by various neurophysiological techniques. Four databases were searched using PRISMA guidelines through February 2016. The inclusion criteria were: CHO as intervention against a placebo control, fatigue induced by prolonged exercise and assessed using neurophysiological measures [voluntary activation (VA), superimposed twitch (SIT), M-wave, electromyography], alongside maximal voluntary contraction (MVC). Seven papers were reviewed, where exercise duration lasted between 115 and 180 min. CHO improved exercise performance in three studies, whereby two of them attributed it to CF via attenuation of VA and SIT reductions, while the other indicated peripheral involvement via attenuation of M-wave reduction. Although a few studies suggest that CHO attenuates CF, data on its direct effects on neurophysiological outcome measures are limited and mixed. Generally, measures employed in these studies were inadequate to conclude central contribution to fatigue. Factors including the techniques used and the lack of controls render additional confounding factors to make definitive deductions. Future studies should employ consistent techniques and appropriate neurophysiological controls to distinguish CHO effect at central level. The use of pharmacological intervention should be incorporated to elucidate involvement of central mechanisms.